Hypothesis: glyphosate-based herbicides can increase risk of hematopoietic malignancies through extended persistence in bone - Charles M. Benbrook (Environmental Sciences Europe)
Abstract Despite episodic and variable patterns of exposure, the levels of glyphosate (GLY) detected in the urine of herbicide applicators and the general public are relatively stable across space (urban vs. rural) and time (weed spray season, not spray season). Substantial GLY metabolism data show that within minutes of entering the bloodstream, GLY moves into bone marrow, and then laterally through bone tissue and back into general circulation. As GLY moves through bone it comes into contact with calcium and a portion is immobilized via chelation. A novel two-part hypothesis is explored: first, the likely reason for the lack of variability in GLY levels in urine is that GLY stored in bone is excreted gradually over days to weeks, and augments the generally stable and modest levels of dietary exposure to GLY; and second, the prolonged systemic movement of GLY into bone marrow and bone extends contact between GLY and hematopoietic stem cells (HSC), increasing the risk of GLY-induced breaks and rearrangements in the DNA in HSCs. Studies confirm that GLY and glyphosate-based herbicides (GBHs) can trigger oxidative stress and impair DNA-repair mechanisms. Animal bioassays and epidemiology studies link GLY/GBH exposures to heightened risk of blood cancers, and possibly other pathologies. The hypothesis proposed here provides a plausible pathophysiologic basis for these observations relative, in particular, to blood cancers.